1988
DOI: 10.1111/j.1600-0528.1988.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation into the validity of dentists' decisions to restore occlusal surfaces of permanent teeth

Abstract: This study investigates the validity of the treatment decisions made by 10 hospital dentists, who examined the fissures of extracted teeth using a visual-only technique. The study shows that 8 of the 10 dentists were more likely to leave carious teeth unrestored than unnecessarily treat sound teeth. The authors suggest that this system of diagnosing occlusal caries is a satisfactory one in terms of its sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…Generally, the participating dentists showed a higher specificity than sensitivity, a pattern also found by Kay et al [1988]. In their study with 10 den tists using the visual technique and 30 teeth, they found an average specificity of 67% and a sensitivity of 57%.…”
Section: Discussionmentioning
confidence: 71%
“…Generally, the participating dentists showed a higher specificity than sensitivity, a pattern also found by Kay et al [1988]. In their study with 10 den tists using the visual technique and 30 teeth, they found an average specificity of 67% and a sensitivity of 57%.…”
Section: Discussionmentioning
confidence: 71%
“…That is, they are willing to miss detecting some lesions (low sensitivity and high specificity) in order not to over treat the disease (high sensitivity and low specificity). Ex perienced dentists who have seen the long-term results of restoration placement (the commitment of a tooth to a life time o f restorative treatment) may be more willing to avoid placement of a restoration in a questionably diseased tooth than to place one in a caries-free tooth [Kay et al, 1988]. In contrast, dental students have not had the experience of ob serving teeth over long periods of time and thus have not seen the long-term consequences of restorative treatment.…”
Section: Discussionmentioning
confidence: 93%
“…It is generally accepted that in the fi eld of caries diagnosis a high specifi city is to be aimed for, as this will reduce unnecessary operative treatment [Kay et al, 1988]. The likelihood ratio unites the values of specifi city and sensitivity simplifying comparison of diagnostic tests or tools but the separate parameters of specifi city and sensitivity should still be considered.…”
Section: Discussionmentioning
confidence: 99%